Effect of filler type, content and size on the UV-curing dental materials - Seghier, Zoubida; Diby, Ambroise; Voytekunas, Vanda; Cheang, Philip; J.M. Abadie, Marc (Publishing House of Lviv Polytechnic National University, 2008)
A bis-GMA, TEGDMA monomer mixture at weight ratio 2:1 was UV-cured with CQ to from commonly used dental materials. Three types of fillers at different particle size were added at different weight concentrations. Reaction rates k, time vs rate were studied for all the systems. Мономерну суміш біс-ГМА і ТГМ-3 із ваговим співідношенням 2:1 затверджували УФ-випромінюванням з камфорохіноном для одержання стоматологічних матеріалів загального використання. Додавались три різних типи наповнювачів, з різними розмірами частин і ваговими концентраціями. Для всіх систем вивчали швидкість реакції та її залежність від тривалості процесу.
Вплив типу, кількості і розміру наповнювача на УФ - затверджувані стоматологічні матеріали
Keywords: UV-curing; filler; kinetics; bis-GMA; TEGDMA; УФ-затверджувач; наповнювач; біс-ГМА; ТГМ-3